A comparative study of the regulatory framework for cosmetics in South Africa, Europe, the United States of America and India - Sukhnandan, Sohana (My University, 2021)
Globalisation has resulted in the world becoming interconnected. The alignment of regulatory frameworks is therefore important to ensure consumer safety and quality products without compromising international trade. As the South African cosmetics market is the largest on the African continent, the South African government has recognised that an improved legislative framework is required and therefore proposed amended regulations to the Foodstuffs, Cosmetics and Disinfectants Act of 1972. This study followed a qualitative, deductive approach utilising a framework analysis and aimed to compare the proposed amended cosmetic regulatory framework for South Africa (SA) to the European Union (EU), United States of America (USA) and India. The results have shown that SA is aligning to the EU cosmetics framework, adopting the positive and negative lists of ingredients, the use of universal INCI (International Nomenclature of Cosmetic Ingredients) terms for ingredient labelling and aligning on product claims which will facilitate harmonisation and reduce trade barriers but has adopted a passive post marketing surveillance system similar to the USA and India. It is recommended that an active surveillance system should be utilised as this will recognise safety trends faster
A research report submitted in fulfilment of the requirements for the degree Master of Science in Medicine (Pharmaceutical Affairs) to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021